A Sporadic Neonatal Case of Epidermolysis Bullosa Simplex Generalized Intermediate with KRT5 and KRT14 Gene Mutations - Wakiguchi, Hiroyuki; Hasegawa, Shunji; Maeba, Shinji; Kimura, Sasagu; Ito, Satoko; Tateishi, Hiroshi; Ueda, Kazuhiro; Ohga, Shouichi (American Journal of Perinatology Reports, 2016)
Background Epidermolysis bullosa simplex (EBS) is a rare genodermatosis resulting from multiple gene mutations, including KRT5 and KRT14. The clinical expression of the mechanobullous skin fragility disease has not been fully explained by the genotype.Case Description An 11-day-old Japanese newborn infant was hospitalized because of herpetiform skin blistering on the feet, which expanded systemically after birth. There was no evidence of virus infection. The biopsied skin lesion showed a blister on the lamina densa without keratin clumps, indicating a diagnosis of EBS-generalized intermediate. We punctured the blisters to remove the contents daily, which led to no exacerbation or infection. The genetic study determined that the patient carried double substitutions of KRT5 c.1424A > G (p.E475G) and KRT14 c.1237G > A (p.A413T). The asymptomatic mother and sister carried the KRT14 substitution, but the healthy father had no substitution of the KRT gene.Conclusion This is the first report of EBS-generalized intermediate in a newborn with de novo KRT5 gene mutation and KRT14 gene polymorphism, and no familial history of epidermolysis. Neonatal blistering due to EBS requires optimal skin management after excluding infectious and immunobullous diseases.
Keywords: epidermolysis bullosa simplex; KRT5; KRT14; mutation; newborn